FARMERS' PERCEPTION OF FACTORS RELATED TO SALON AGRIBUSINESS IN THE FOOD ESTATE AREA IN HUMBANG HASUNDUTAN REGENCY - Bahagia; Tavi Supriana; Diana Chalil (CV. Radja Publika, 2023)
The food estate program is a government program made for Humbahas farmers as a food barn where one of their commodities is shallots. Shallot marketing is difficult due to the incomplete involvement of cooperation between stakeholders. The purpose of this study is to analyze farmers' perceptions of internal and external factors related to shallot agribusiness in the food estate area in Humbang Hasundutan Regency. The method of analysis of this research is descriptive quantitative analysis using a Likert scale measurement, using a questionnaire (questionnaire) on the components of internal and external indicators. The results showed that the level of farmers' perceptions of factors was relatively high. With an average score for internal factors of 3.18 and an average score for external factors of 2.70. Internal factors that have the highest influence on shallot farmers are land clearing capital from the government, production inputs supplied by investors and cross-road infrastructure that has been built. While the external factors that have the highest influence are the greater employment opportunities for farmers and the food estate agricultural technology used. Meanwhile, the factors that need attention are the price of shallots, the percentage of the profit sharing system, marketing of shallots and cooperation agreement contracts. While the external factors that have the highest influence are the greater employment opportunities for farmers and the food estate agricultural technology used. Meanwhile, the factors that need attention are the price of shallots, the percentage of the profit sharing system, marketing of shallots and cooperation agreement contracts. While the external factors that have the highest influence are the greater employment opportunities for farmers and the food estate agricultural technology used. Meanwhile, the factors that need attention are the price of shallots, the percentage of the profit sharing system, marketing of shallots and cooperation agreement contracts.